Strategic watch: a risk management system in exporting SMEs - Ibrahim ASSABANE; Said MSSASSI (Journal of Information Sciences, 2022)
The objective of this paper is to highlight the role that strategic intelligence could play, as a catalyst for anticipatory information, in the management of export risks in SMEs and the skills that leaders and entrepreneurs must have to succeed in their information behaviors. The theoretcal contribution of this work lies in the implementaton of a new conceptualization of the strategic intlligence system, hitherto limited to the factors influencing its implementation among senior managers, in the analysis of its interaction with environmental sectors. The use of strategic intelligence in SMEs instead of outsourcing it to external organizations, of relational capital instead of physical capital, of information resources instead of financial and technical resources offers a new organizational and strategic mode of operation for SMEs operating in international markets with inherent risks